Activation of Autophagy Relieves Linoleic Acid-Induced Inflammation in Large Yellow Croaker (Larimichthys crocea) - Yang, Bo; Ji, Renlei; Li, Xueshan; Fang, Wei; Chen, Qiuchi; Chen, Qiang; Xu, Wei; Mai, Kangsen; Ai, Qinghui (Frontiers in Immunology, 2021)
High levels of soybean oil (SO) in fish diets enriched with linoleic acid (LA, 18:2n-6) could induce strong inflammation. However, the molecular mechanism underlying LA-induced inflammation in the liver of large yellow croaker (Larimichthys crocea) has not been elucidated. Based on previous research, autophagy has been considered a new pathway to relieve inflammation. Therefore, the present study was performed to investigate the role of autophagy in regulating LA-induced inflammation in the liver of large yellow croaker in vivo and in vitro. The results of the present study showed that activation of autophagy in liver or hepatocytes could significantly reduce the gene expression of proinflammatory factors, such as tumor necrosis factor α (TNFα) and interleukin 1β (IL1β). The results of the present study also showed that inhibition of autophagy could upregulate the gene expression of proinflammatory factors and downregulate the gene expression of anti-inflammatory factors in vivo and in vitro. Furthermore, autophagy could alleviate LA-induced inflammatory cytokine gene expression in vivo and in vitro, while inhibition of autophagy obtained the opposite results. In conclusion, our study shows that autophagy could regulate inflammation and alleviate LA-induced inflammation in the liver of large yellow croaker in vivo and in vitro for the first time, which may offer considerable benefits to the aquaculture industry and human health.